Intraoperative dynamics of interleukin-6 levels during planned coronary stenting with different approaches to analgesic sedation - D.О. Dziuba (Кардіохірургія та інтервенційна кардіологія)
The aim – to study the dynamics of the level of interleukin-6 (IL-6) under various drugs for analgesic sedation in the perioperative period of planned coronary stenting.